Transmission routes of chronic hepatitis C and their relation to HCV genotypes - (:unkn) unknown (My University, 2010)
Amaç: Kronik hepatit C'li hastalarda hepatit C virusunun bulaş yolları araştırılmış ve virusun genotipleri ile bulaş yolları arasındaki ilişki incelenmiştir. Yöntem ve Gereç: Genotipleme,revers hibridizasyon, Line Probe assay, yöntemi ile gerçekleştirilmiştir. Bulgular: 108 HCV RNA pozitif hastada, dört farklı genotip ve bazı mix genotipler saptanmıştır.1b genotipi en yaygın genotip olarak bulunmuştur (n=82) Hastaların altısının 1a, altısının 3a, dördünün 2a/2c, üçünün 2a, birinin 4c/4d genotipinde oldu¤u belirlenmiştir. Altı hastada, üçü genotip 1a+1b, ikisi genotip 1b+4a, biri ise genotip 1b+2a şeklinde, mikst genotip saptanmıştır.Altı hastada mikst genotip belirlenmiştir. Bunların üçü 1a+1b, ikisi 1b+4a, biri de 1b+2a/2c genotipinde saptanmıştır. Bütün hasta gruplarında en yaygın genotip 1b idi.108 hastanın %38.8'inde kan ve kan ürünleri transfüzyonu, %16.6'sında cerrahi girişim, %15.7'sinde diş tedavisi ve %12.9'unda diyaliz öyküsü mevcuttu. Sonuç: Kan donörlerinde rutin kan testleri yaptırmaları zorunlu olmadan önce, HCV infeksiyonunun en yaygın bulaşma yolu kan transfüzyonu ile olmaktaydı. Çalışmamızda,dövme, piercing, iatrojenik infeksiyonlar ve damar içi ilaç kullanımı gibi, bulaş açısından risk faktörlerinin hiçbiri bu hastalarda kaydedilmemiştir. Cerrahi işlem öyküsü bulunan hastalarda en yaygın genotip 1b saptanmıştır. Tüm hasta populasyonunda genotip 1b %75.9 oranında saptanmıştır.

Background/aims: Hepatitis C virus transmission routes in chronic hepatitis C patients, the relationship between the viral genotype and the transmission routes were studied. Material and Methods: Genotyping was performed by using a commercial reverse hybridization method, Line Probe Assay. Results: Genotyping of 108 HCV RNA positive patients revealed four different types (1,2,3, and 4) and some mixed types. Subtype 1b was the most common (n=82). Subtype 1a and 3a were detected in six patients, 2a/2c was detected in seven patients, and 4c/4d was detected in one patient respectively. Six subjects revealed mixed infections. Three of them were 1a+1b, two of them were 1b+4a, and one of them was 1b+2a/2c.Genotype 1b was most common in all groups.In 38,8% of the 108 patients with a history of blood or blood product transfusions,16,6% of patients with a history of surgery, 15,7% of patients had an anamnesis of dental treatment and, 12,9% of patients receiving dialysis. Conclusion: Before the routine screening of blood donor practices became mandatory, the most common route of HCV infection was blood transfusions. The other risk factors of transmission such as tattoos, piercings, iatrogenic infections and intravenous drug usage have not been recorded for any of these patients in our study. The patient with a history of surgery had the genotype 1b as the most common genotype. The genotype 1b was determined in 75,9% of the whole patient population of the study.
Kronik hepatit C virus infeksiyonlu hastalarda infeksiyon kaynakları ile hepatit C virus genotipleri arasındaki ilişki
Keywords: Cerrahi